2015
DOI: 10.1021/acs.chemmater.5b00583
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Vapor-Deposited Glasses of an Organic Hole Transport Material with X-ray Scattering

Abstract: Vapor-deposited organic glasses can be produced with enhanced thermal stability and tunable molecular orientation by controlling the substrate temperature during deposition. Recent work has also shown improved charge carrier mobility associated with anisotropic molecular packing in organic electronics. Here grazing-incidence wide-angle X-ray scattering (GIWAXS) is used to characterize the structural anisotropy in glasses of a hole transport material, N,N′-bis(3-methylphenyl)-N,N′-diphenylbenzidine, commonly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 43 publications
12
79
0
Order By: Relevance
“…23 To carry out this study, we have chosen the organic semiconductor TPD (N,N 0 -bis(3-methylphenyl)-N,N 0 -diphenylbenzidine), and the pharmaceutical molecule IMC (1-(4-Chlorobenzoyl)-5methoxy-2-methyl-3-indoleacetic acid), as they form glasses with enhanced stability and have been widely characterised as a function of deposition temperature. 2,3,15,16,22,[24][25][26][27][28][29][30] IMC shows a maximum of stability when deposited around 266 K (0.85T g ) 26 and a transition into the supercooled liquid governed in the first stages by a transformation front whose velocity depends on the deposition conditions of the IMC glass. 15,26 Spectroscopic ellipsometry measurements of thin film TPD glasses have shown that TPD also transforms via a propagating front under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…23 To carry out this study, we have chosen the organic semiconductor TPD (N,N 0 -bis(3-methylphenyl)-N,N 0 -diphenylbenzidine), and the pharmaceutical molecule IMC (1-(4-Chlorobenzoyl)-5methoxy-2-methyl-3-indoleacetic acid), as they form glasses with enhanced stability and have been widely characterised as a function of deposition temperature. 2,3,15,16,22,[24][25][26][27][28][29][30] IMC shows a maximum of stability when deposited around 266 K (0.85T g ) 26 and a transition into the supercooled liquid governed in the first stages by a transformation front whose velocity depends on the deposition conditions of the IMC glass. 15,26 Spectroscopic ellipsometry measurements of thin film TPD glasses have shown that TPD also transforms via a propagating front under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…47 Grazing-incidence x-ray scattering measurements on N,N ′ -bis(3-methylphenyl)-N,N ′ -diphenylbenzidine (TPD) indicate anisotropy in nearest-neighbor packing that depends upon substrate temperature during deposition. 48 Based on these last two studies, it has been suggested that anisotropic packing is not a necessary condition for high kinetic stability, but rather that these two properties are independent features of the vapor deposition process. A recent analysis of model PVD polymer glasses reinforces that view.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the structure–molecular orientation relationships, we analyzed GIWAXD images to obtain the order parameter ( S ) according to the method reported by Hammond et al and Gujral et al (Figures S25–S28, Supporting Information) . This order parameter can be calculated based on the diffraction near q ≈ 1.65 Å −1 and is defined as followsSGIWAXD=123cos2ω1…”
mentioning
confidence: 99%